2022
DOI: 10.1021/jacs.2c03113
|View full text |Cite
|
Sign up to set email alerts
|

Revitalizing Iron Redox by Anion-Insertion-Assisted Ferro- and Ferri-Hydroxides Conversion at Low Alkalinity

Abstract: Iron hydroxides are desirable alkaline battery electrodes for low cost and environmental beneficence. However, hydrogen evolution on charging and Fe3O4 formation on discharging cause low storage capacity and poor cycling life. We report that green rust (GR) (Fe2+ 4Fe3+ 2 (HO–)12SO4), formed via sulfate insertion, promotes Fe­(OH)2/FeOOH conversion and shows a discharge capacity of ∼211 mAh g–1 in half-cells and Coulombic efficiency of 93% after 300 cycles in full-cells. Theoretical calculations show that Fe­(O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The discharge plots in Figure b indicate that during in-system GCD activation, the areal capacity of H-Fe 3 O 4 @Fe foam electrode gradually increased, and the ever-increasing plateau suggests that the material undergoes inherent evolution and reconstruction on interface engineering. According to previous reports, these two typical discharge plateaus at ∼−1.04 and −0.8 V (vs Ag/AgCl) are assigned to Fe 0 → Fe 2+ and Fe 2+ → Fe 3+ anodic reactions, respectively. , Besides, the electrochemical double-layer capacitance ( C dl ) is measured to assess electrochemical surface area (ECSA) using a selected-potential cyclic voltammetry (CV) technology (Figures c and S3). Figure c demonstrates that the electrode under different scanning rates records rectangular shape, representing characteristic double-layer capacitance.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…The discharge plots in Figure b indicate that during in-system GCD activation, the areal capacity of H-Fe 3 O 4 @Fe foam electrode gradually increased, and the ever-increasing plateau suggests that the material undergoes inherent evolution and reconstruction on interface engineering. According to previous reports, these two typical discharge plateaus at ∼−1.04 and −0.8 V (vs Ag/AgCl) are assigned to Fe 0 → Fe 2+ and Fe 2+ → Fe 3+ anodic reactions, respectively. , Besides, the electrochemical double-layer capacitance ( C dl ) is measured to assess electrochemical surface area (ECSA) using a selected-potential cyclic voltammetry (CV) technology (Figures c and S3). Figure c demonstrates that the electrode under different scanning rates records rectangular shape, representing characteristic double-layer capacitance.…”
Section: Resultsmentioning
confidence: 77%
“…According to previous reports, these two typical discharge plateaus at ∼−1.04 and −0.8 V (vs Ag/AgCl) are assigned to Fe 0 → Fe 2+ and Fe 2+ → Fe 3+ anodic reactions, respectively. 46,47 Besides, the electrochemical double-layer capacitance (C dl ) is measured to assess electrochemical surface area (ECSA) using a selected-potential cyclic voltammetry (CV) technology (Figures 1c and S3). 48 Figure 1c demonstrates that the electrode under different scanning rates records rectangular shape, representing characteristic double-layer capacitance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that the insertion of SO 4 2− anions into Fe(OH) 2 , a brucite-type layered double hydroxide (LDH), assisted the conversion of Fe(OH) 2 into FeOOH during the electro-oxidation process in an alkaline solution. 24 Anion-intercalated Fe(OH) 2 is called green rust (GR), having a chemical formula of [Fe 1−x 2+ Fe 3+ x (HO − , and Cl − transport in interlayers of LDHs has a lower percolation barrier. Second, the monovalent nature of Cl − causes less drastic distortion of the Fe−O molecular framework due to their modulated electrostatic interaction, in stark contrast to the strong interaction between divalent SO 4 2− and positively charged Fe−O molecular framework.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several studies have studied the structure–property relationships involved during the Cl – transport in LDHs, , though explicit structural evidence from in situ and operando studies is still lacking. Recently, it was reported that the insertion of SO 4 2– anions into Fe­(OH) 2 , a brucite-type layered double hydroxide (LDH), assisted the conversion of Fe­(OH) 2 into FeOOH during the electro-oxidation process in an alkaline solution . Anion-intercalated Fe­(OH) 2 is called green rust (GR), having a chemical formula of [Fe 1– x 2+ Fe 3+ x (HO – ) 2 ] x + (A x / n n – ) x − , where anions (A n – ) are intercalated between the Fe–O interlayers.…”
Section: Introductionmentioning
confidence: 99%